Impact of small-scale geometric roughness on wetting behavior - Kumar, Vaibhaw (Langmuir : the ACS journal of surfaces and colloids, 2013)
We examine the extent to which small-scale geometric substrate roughness influences the wetting behavior of fluids at solid surfaces. Molecular simulation is used to construct roughness wetting diagrams wherein the progression of the contact angle is traced from the Cassie to Wenzel to impregnation regime with increasing substrate strength for a collection of systems with rectangularly shaped grooves. We focus on the evolution of these diagrams as the length scale of the substrate features approaches the size of a fluid molecule. When considering a series of wetting diagrams for substrates with fixed shape and variable feature periodicity, we find that the diagrams progressively shift away from a common curve as the substrate features become smaller than approximately 10 fluid diameters. It is at this length scale that the macroscopic models of Cassie and Wenzel become unreliable. Deviations from the macroscopic models are attributed to the manner in which the effective substrate-fluid interaction strength evolves with periodicity and the important role that confinement effects play for substrates with small periodicities